2013
DOI: 10.1007/s00228-013-1506-8
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medication use among patients with Alzheimer disease in the REAL.FR cohort: be aware of atropinic and benzodiazepine drugs!

Abstract: These results reveal that approximately one out of two community-dwelling patients with mild-to-moderate AD treated by AD specialists use PIMs. They also indicate that the characteristics of the disease and the pharmacodynamic/pharmacokinetic profile of the drugs prescribed are not sufficiently taken into account by physicians when prescribing for AD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 37 publications
3
76
2
1
Order By: Relevance
“…While some variability can be expected because of differences in the criteria the various tools employ-for example, in drug-disease interactions and dosing limits for certain drugs-the ability to apply criteria consistently across studies was also not possible because of the availability of certain drugs in different countries (Appendix 1). The variability in the prevalence of potentially inappropriate medications based on the tool used to detect it is illustrated dramatically in Montastruc et al 's study 27 25 this may have been driven by the use of estrogens among women. Indeed, when the authors analyzed the data based on a model in which they removed estrogen use, no significant differences were found between men and women in potentially inappropriate medication use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some variability can be expected because of differences in the criteria the various tools employ-for example, in drug-disease interactions and dosing limits for certain drugs-the ability to apply criteria consistently across studies was also not possible because of the availability of certain drugs in different countries (Appendix 1). The variability in the prevalence of potentially inappropriate medications based on the tool used to detect it is illustrated dramatically in Montastruc et al 's study 27 25 this may have been driven by the use of estrogens among women. Indeed, when the authors analyzed the data based on a model in which they removed estrogen use, no significant differences were found between men and women in potentially inappropriate medication use.…”
Section: Discussionmentioning
confidence: 99%
“…This significant association remained after a multivariate analysis was conducted (OR = 3.6, 95% CI = 2.6-4.5). 27 In Pugh et al 's study, 28 the number of unique medications was identified as a risk factor for drug-disease interactions among dementia patients (OR = 1.13, 95% CI = 1.12- …”
Section: Medication Usementioning
confidence: 98%
See 1 more Smart Citation
“…The publication of studies increased over time; there was one paper published in 2002 (earliest included paper) [18] and five in 2013 [19-23] (Tables 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] There is additional concern about the association between BZD use and cognitive decline in Alzheimer's disease. [10][11][12][13] Patients with stroke suffer from major comorbidities, including cardiac arrhythmias and sleep-related hypoxaemia. 14 Few studies have addressed the effect on mortality when using antidepressants in patients with post-stroke.…”
Section: Introductionmentioning
confidence: 99%